Sejarah monumen tugu pahlawan Palagan Mendalan di kecamatan Ngantang - setyo, jofan amirul (Maliki Interdisciplinary Journal, 2025)
This study aims to uncover the history, meaning, and values ​​of the struggle contained in the Palagan Mendalan Heroes Monument located in Ngantang District, Malang Regency. This monument was built to commemorate the heroic battle of 1947 under the leadership of Lieutenant Anumerta Soediarto, which became a symbol of the tenacity of the people of Ngantang and Kasembon in defending Indonesia’s independence from Dutch colonialism. This study used a descriptive qualitative approach with data collection techniques through field observations, interviews with local residents, and literature studies from various historical sources and scientific journals. The results of the study indicate that the Palagan Mendalan Monument not only has historical value, but also educational, social, and spiritual value, because it can be a medium for learning local history as well as a means of instilling national character. This monument plays an important role in strengthening the public’s historical awareness and nationalism, and is a symbol of regional pride that must be preserved. Thus, the preservation of this monument is very important through educational activities, research, and the promotion of historical tourism so that the younger generation can continue to appreciate the struggle of the heroes and emulate their fighting spirit in the life of the nation and state.